P3.376 Multidisciplinary Approach to Contain HIV-1 and Other STIs in China: Multipurpose Prevention Technologies. (13th July 2013) - Wu, Z; Holt, B Young; Manning, J; Romano, J; Lusti-Narasimhan, M; Stone, A; Deal, C; Wang, B
Abstract : Background: In China, the HIV prevalence continues to rise despite increasing efforts to contain the epidemic, and other sexually transmitted infections (STIs) are also on the increase. Furthermore, antibiotic-resistant STI pathogens are on the increase and many STIs facilitate the acquisition and/or transmission of HIV-1. Multipurpose prevention technologies (MPTs), including drugs, devices and vaccines that simultaneously prevent unintended pregnancies, HIV and other STIs, would provide effective approaches to meet these public health challenges. Methods: The Initiative for MPTs developed Target Product Profiles (TPPs) to define key product attributes appropriate for those regions of the world hardest hit by unintended pregnancy, HIV, and other STIs. The TPP considered priority combinations of indications, mechanisms of action, dosing and administration, and formulation and delivery. Current and historic data from China were reviewed to determine which product attributes in an MPT would best meet the needs in China. Results: Sexual transmission of HIV-1 has become the major route for new infection in China, and other STIs have increased more than 40 times from 1985. The increase in STI rates is associated with population mobility, and the geographic distribution of STIs overlaps with that of HIV, suggesting the possibility of co-infection. The rate of unintended pregnancy is low in China, given the "one child" policy. After analysing the current and historic data, we propose that MPTs specifically addressing HIV and STIs would best meet the public health challenges in China, and the preferred dosing form would be long-acting implant or IUD-based delivery. Conclusion: The continuing rise in prevalence and rates of STIs, including HIV poses serious public health challenges to China, where sustained economic development has resulted in social transformation and unprecedented population mobility. MPTs that specifically target HIV and other STIs could provide an effective approach to meeting these public health challenges in China.